Confirming correctness of procedure for determining soft parameters in Coulomb potential of noble atoms - Truong, Thu D. H.; Ho, Bach N. X.; Do, Tai V. (Hue University Journal of Science: Natural Science, 2024)
This paper verifies that the procedure described in [Computer Physics Communications, 276, 108372 (2022)] for determining the soft parameters in the Coulomb potential of noble atoms is accurate via the modification of the initial position value of x0 and the parameter b range. In the case of nonsequential double ionization (NSDI), the results demonstrate that the value of x0 is not contingent upon the range of computed parameter a. Furthermore, we examine the significance of parameter b in the NSDI process and conclude that the ideal value for the soft Coulomb parameter of b is that b ≤ 0.1 a.u.